2009
DOI: 10.1164/rccm.200903-0421oc
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Decision Aid for Patients with Cystic Fibrosis Considering Lung Transplantation

Abstract: Use of a decision aid for patients with cystic fibrosis considering referral for lung transplantation, in addition to usual education and counseling, improves patient knowledge, realistic expectations, decisional conflict, and patient satisfaction. Clinical trial registered with www.clinicaltrials.gov (NCT00345449).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 13 publications
1
75
0
Order By: Relevance
“…Patients were not blinded, as this is inherent to the intervention evaluated. Blinding of the care providers was impossible in some studies, 23,25,27,29,31,33 as they were involved in providing the decision aid. It was unclear whether outcome assessors were blinded to the intervention.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were not blinded, as this is inherent to the intervention evaluated. Blinding of the care providers was impossible in some studies, 23,25,27,29,31,33 as they were involved in providing the decision aid. It was unclear whether outcome assessors were blinded to the intervention.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…Twelve studies reported on the treatment options chosen by patients and their surgeons 19,21,[23][24][25][26][27]29,[31][32][33][34] A total of 473 of 1451 patients (33%) who had used a decision aid chose to undergo the invasive treatment option, whereas 539 of 1223 patients (44%) in the control groups made the same decision, resulting in an absolute difference of 11% and a risk ratio of 0.80 (95% CI, 0.67-0.95) (Fig. 3).…”
Section: Effects Of Decision Aidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six of the 61 studies involved a patient decision aid [16,18,20,22,25,32,33,[47][48][49][50][51][52][53]56,[58][59][60][61]64,66,68,[72][73][74][75]. Four additional studies reported using education materials such as educational sessions or pamphlets but did not refer to them as decision aids [17,43,63,70].…”
Section: Summary Of Included Articlesmentioning
confidence: 99%
“…Thirty of the 61 studies reported assessment of the subjects' knowledge surrounding the decision [16,18,20,22,25,32,33,44,[47][48][49]51,53,[56][57][58][59][60][61][64][65][66]68,[71][72][73][74][75]77,78]. The majority of these studies (n = 27) used decision-specific items, while three [71,77,78] used generic measurements, e.g.…”
Section: Measuring Knowledgementioning
confidence: 99%